Concept of Basti – A Review - SUDHAKARAN, DR. KEERTHI (International Research Journal of Ayurveda & Yoga, 2025)
Three key Ayurvedic principles are Samshodhana (therapeutic purification), Samshamana (palliative treatment), and Nidana Parivarjana (avoid causative causes) in the management of disorders. With five well-planned treatments for internal body cleaning through the closest route, Panchakarma offers a distinctive take on Ayurveda. Basti Chikitsa is considered the most effective Panchakarma treatment method. Being an eternal science, “Ayurveda,” the “science of human life,” deals with the physical, psychological as well as spiritual well-being of an individual. It covers all the spheres of human life. The importance of Basti is highlighted as much as to call it half of the treatment. It is the best therapy to regulate the vata dosha which is the chief governing force behind all the physiological and pathological processes both in the body and mind. Basti Chikitsa is not only best for Vata dosha disorders but also cures the Pitta dosha, Kapha dosha, Sansargajanya dosha, and Raktgata dosha disorders. It is also useful to treat Shakhagat, Koshthagat, and Tiryak Margagat diseases.